A Model of Work Related Self-Directed Learning (WRSDL) as the Basis for Organizational Learning - Ida Juliana, Hutasuhut; Sopian, Bujang; Shahren Ahmad, Zaidi Adruce; Hasbee, Hj Usop (2016)
This study focuses on the work-related self-directed learning (WRSDL) practices in order to capture a comprehensive understanding regarding the phenomena. Considering that there has been no solid theory about WRSDL, it is necessary to conduct an explorative study that shall provide a rich data in order to strengthen the body of knowledge. This explorative study using qualitative method was conducted in examining WRSDL practices among staffs and managers from various departments in a private organization in Indonesia. This organization has been chosen deliberately by knowing that being a learning organization is one towards the goal to be achieved. In this organization, improvement and innovation have always been the central issues and become a way of life ingrained among employees. A total of thirty staffs and managers were purposively selected and interviewed in-depth using the semi-structured approach. The rich data gathered were analyzed using content analysis technique. This study resulted in the construction of a conceptual model of WRSDL that highlights three important factors; the driving factors, the barriers, and the preferred learning practices. This model shows the dynamic interaction of these three factors and indicates the benefits and ways how to cultivate WRSDL in an organization. Implications of the model to the body of knowledge, future research and practitioner are provided at the end of the paper.